Pengaruh Disiplin Kerja Dan Beban Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Perencanaan Dan Penelitian Kabupaten Sikka - Maria Handayani Yunita Wale; Maria Silvana Mariabel Carcia; Yustina Olivia Da Silva (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This study aims to (1) To find out how the description of employee performance, work discipline and workload. (2) To determine the effect of work discipline and workload on employee performance either partially or simultaneously. The population in this study were 56 employees who worked at the Sikka Regency Planning and Research and Development Office. The sample used was the saturated sample technique so that the total sample size of less than 100 was used entirely by the researcher, namely 56 employees. The results of the descriptive statistical analysis show that employee performance, work discipline, and workload are categorized as good. The statistical results of the t-test show that partially the work discipline variable has a significant effect on employee performance. The statistical results of the F test show that work discipline and workload simultaneously have a significant effect on employee performance. The determination result is 0.715 which means that the contribution of work discipline and workload variables to employee performance is 51.2%.